Baby & child question & answer - Cooper, Carol 1951- (London Dorling Kindersley, 2005)
Provides: solutions to everyday problems on various aspects of baby and childcare, for children aged 0-5 - from feeding and sleeping to toddler tantrums and coping with childhood ailments
Family corner
Includes bibliographical references and index
1 9
Keywords: Child care; Infants -- Care; Infants' supplies Environmental aspects